2010
DOI: 10.1021/bm1000907
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Solvents and Temperature on the Conformation of Poly(β-benzyl-l-aspartate) Brushes

Abstract: We report on the synthesis and characterization of end-tethering polypeptide monolayers based on poly(beta-benzyl-L-aspartate) (PBLA) homopolymer and PBLA-b-poly(gamma-benzyl-L-glutamate) block copolymer. The homopolypeptide and copolypeptide brushes were fabricated by the sequential, surface-initiated vapor deposition polymerization of the N-carboxyanhydride of beta-benzyl-L-aspartate or gamma-benzyl-L-glutamate, yielding 80-nm-thick, chemically grafted films after 30 min of reaction time. Both Fourier transf… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
34
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 28 publications
(36 citation statements)
references
References 43 publications
2
34
0
Order By: Relevance
“…In our experiments, the micelles of all the graft copolymers were thermoresponsive (summarized in Table 2). As a typical example shown in Figure 8(F), with the increase of temperature from 25 to 60 C, the R h of PLG 44 R h is attributed to the rapid hydration-to-dehydration transition of OMEO 3 MA when the temperature increases and the existence of oligo(ethylene glycol) (MEO 3 ) that could prevent the intermicellar aggregation at the temperature even above the LCST of the copolymer. This phenomenon was just opposite to the result of the previous report of literature.…”
Section: Cmc Values (Listed Inmentioning
confidence: 93%
See 1 more Smart Citation
“…In our experiments, the micelles of all the graft copolymers were thermoresponsive (summarized in Table 2). As a typical example shown in Figure 8(F), with the increase of temperature from 25 to 60 C, the R h of PLG 44 R h is attributed to the rapid hydration-to-dehydration transition of OMEO 3 MA when the temperature increases and the existence of oligo(ethylene glycol) (MEO 3 ) that could prevent the intermicellar aggregation at the temperature even above the LCST of the copolymer. This phenomenon was just opposite to the result of the previous report of literature.…”
Section: Cmc Values (Listed Inmentioning
confidence: 93%
“…43 These characteristic ellipticities suggested that the secondary structures of graft copolymers were right-handed a-helix. 44 As shown in Figure 6(A) and Table 2, the molar ellipticities at 222 nm ([h] 222 ) of PLG 44 -g-OMEO 3 MA 4 at 25 and 60 C, as well as, PLG 44 -g-OMEO 3 MA 7 , PLG 44 -g-OMEO 3 MA 10 , and PLG 67 -g-OMEO 3 MA 3 at 25 C calculated based on the Supporting Information eq S1, and CD spectra were 42,400, 41,020, 39,090, 31,350, and 42,400 deg cm 2 dmol À1 , indicating that the a-helical contents were 100, 100, 97.7, 78.4, and 100%, respectively. By comparison, the temperature and the length of PLGA backbone showed less effect on the content of a-helix, whereas the a-helical content decreased from 100 to 78.4% with increasing DP of OMEO 3 MA from 4 to 10.…”
Section: Secondary Structure Characterizations Of Graft Copolymersmentioning
confidence: 99%
“…[45] The CD spectra (Figure 4) of PLG-g-PMEO 2 MA in aqueous solution with a concentration of 0.04 g Á L À1 had one maximum (l ¼ 192 nm) and two negative minima (l ¼ 208 and 222 nm), suggesting that the secondary structure of the copolymer was a right-handed a-helix. [46,47] In addition, the molar ellipticity of PLG-g-PMEO 2 MA at 222 nm ([u] 222 ) calculated based on Equation S1 and CD spectra at 25 and 60 8C were $267 300 and $178 000 deg Á cm 2 Á dmol À1 , respectively, indicating that the copolymers were almost 100% a-helix in aqueous solution at 25 and 60 8C. [26,48] In summary, PLG-g-PMEO 2 MA can form stimuli-responsive nanoparticles with an a-helical core and a thermo-responsive shell in water (Scheme 2).…”
Section: Turbidimetric Measurementmentioning
confidence: 99%
“…14, [16][17][18][19][20] In this work, we intend to develop a strategy to employ the SI-VDP of NCA amino acids as a convenient approach to create high MW polypeptides. Specifically, high surface area with the cleavable initiator coated PS resin beads are used for the SI-VDP to create high density PBLG brushes in vacuo (Scheme 1); subsequently, the PBLG may be eluted and collected in bulk.…”
Section: 12mentioning
confidence: 99%